T. S. Eliot: love in a world without objects - Brooker, Jewel Spears (Studia Anglica Posnaniensia, 2025)
T. S. Eliot’s early triumphs as a poet are inseparable from his sensuous apprehension of everyday objects from the streets and drawing rooms of the cities in which he spent his youth. His graduate work in philosophy at Oxford includes a theoretical analysis of objects, and his early literary criticism includes several discussions of the importance of balancing subjects and objects, notably the formulation of the “objective correlative” in a 1919 essay on Hamlet. In 1926, in a series of eight lectures at Cambridge University (the Clark Lectures), he addressed the breakdown of objectivity associated with Descartes and, using the poetry of Dante and Donne, explored the deleterious effect of the Cartesian moment on the poetry of love. My aim in this paper is to demonstrate the essential continuity between art and ideas – that is, between Eliot’s poetry and his early work in philosophy.